Rethinking language education, creativity and technology: perspectives and practices - Kassim, Hafizoah (Penerbit UMPSA, 2024)
This book, Rethinking Language Education, Creativity and Technology: Perspectives and Practices, invites readers on a transformative journey into the evolving landscape of language education. Combining innovative insights and practical strategies, it explores how creativity and technology reshape teaching and learning processes. Scholars and educators contribute diverse perspectives, challenging conventional paradigms and proposing dynamic, learner-centered approaches. The book examines effective practices and emerging trends, encouraging educators, researchers, and policymakers to reimagine educational possibilities. Embracing change and fostering creativity, this volume serves as a vital resource for anyone passionate about advancing language education in the digital age and inspires transformative educational futures.